Aprendizaje de políticas y COVID-19: La experiencia de vacunación en países latinoamericanos - Paz-Gómez, Diana Marcela (2024)
This article analyses policy learning processes in decision-making during the process of vaccination against COVID-19, defined in two phases: vaccine procurement and vaccination campaigns, in Latin American countries. On the one hand, it is argued that some of the strategies implemented are explained through policy diffusion mechanisms. Among these, we can consider the definition of priority population groups or the implementation of doses through COVAX. Other measures derive from the operational capacities previously created by governments, such as the deployment of mobile, cross-border or awareness-raising vaccination and health campaigns to address previous infections in the region. Methodologically, a descriptive review of the COVID-19 vaccine supply chain is proposed based on institutional information. In addition, reflections are made on the need for governments to acquire knowledge from their own or others’ experiences to strengthen the health system in the region.